Behavioural response to anthropogenic habitat disturbance: Indirect impact of harvesting on whinchat populations in Switzerland. (June 2015) - Grüebler, Martin U.; Schuler, Heidi; Spaar, Reto; Naef-Daenzer, Beat
Highlights: Harvest of fields destroys nests and surrounding habitats in farmland birds. The whinchats' response to anthropogenic nest loss depends on the remaining habitat. Harvesting patterns affect spatial dynamics and productivity of whinchat populations. Harvesting large areas increased within-season dispersal and reduced re-nesting. Behavioural responses should be considered in the conservation of farmland birds. Abstract: Harvesting often results in the destruction of both, the nest and the surrounding habitat of ground-nesting farmland birds. While the direct effect of harvesting on nest loss and productivity is well investigated, the behavioural responses of parent birds to harvest events remain ambiguous, though they might have profound consequences for farmland bird populations. The progressive harvest of fields within a pair's home-range represents a gradual decrease in habitat quality. The response of breeding individuals to anthropogenic nest loss therefore might depend on the extent of remaining suitable habitat. Here, we radio-tracked a cohort of breeding whinchats Saxicola rubetra affected by anthropogenic nest loss due to harvesting. We used the meadow management as a natural experiment, destroying nests at various stages of the mowing process and leaving different relict areas of suitable habitat after nest loss. Divorce and within-season dispersal rates after nest loss were strongly increased in home-ranges with a high proportion of mown area. Re-nesting rates were six times higher in non-dispersing than in dispersing individuals. Thus, dispersing individuals contributed only little to the overall re-nesting rate and to the productivity of the population. This suggests that the habitat-dependent behavioural responses to harvesting can have major effects on farmland birds' reproductive output. Since harvesting in agricultural landscapes affects many breeding pairs, the resulting changes in the social patterns, the spatial dynamics and the re-nesting rate should be considered in the conservation of farmland bird populations.